Glasses on the nanoscale - Eckert, Hellmut; Ribeiro, Sidney J. L. [UNESP]; Santagneli, Silvia H. [UNESP]; Nalin, Marcelo; Poirier, Gael; Messaddeq, Younès (Springer Nature, 2013)
Homogeneity is supposed to be a particular feature of glasses leading to the well-known isotropic optical properties and mechanical behavior. However, in some cases heterogeneity can be detected at the molecular scale. Amorphous phase separation, incipient crystallization, and concentration gradients are representative of heterogeneities that can be exploited in the preparation of nanostructured glass-derived materials. Nuclear magnetic resonance (NMR) is one of the spectroscopic methods widely used for characterization of the structure of glassy materials, and the basis of new NMR techniques for study on the medium range is first presented in Sect. 18.1. Afterwards, nanoceramics with small crystal volume fractions and crystal dimensions of some nanometers are described, displaying new emerging properties (Sect. 18.2). Metal nanoparticles, quantum dots, and lanthanide-containing nanocrystals are some of the structures that can be grown in glasses (Sect. 18.2). Glasses are unique in the sense that they can be obtained in any morphology, and a final perspective is presented for glass waveguides containing these nanoscale heterogeneities (Sect. 18.3).